Studies on the VO-TiO System. IV. Oxygen Chemisorption - L. Rey; R. Martino; L. Gambaro; H. Thomas (Adsorption Science & Technology, 1988)
The chemical adsorption of oxygen on V 2 O 5 and V 2 O 5 -TiO 2 over the temperature range 100–450°C and at pressures between 10 −2 and 3 Torr has been studied. Assays have been performed using a volumetric method, the isotherms obtained being in accordance with Langmuir's adsorption model. Isobaric plots at 1.5 Torr of these isotherms exhibit two maxima, at 250 and 400°C, respectively. These maxima have been interpreted in terms of the surface chemisorption of O 2− and its diffusion into the bulk solid. The amount adsorbed at the 250°C maximum depends on the sample composition in the following decreasing adsorption order: VT80, VT50, VT10, VT20 and VT0. At the 400°C maximum, the same amount of O 2 is adsorbed experimentally by all the TiO 2 -containing samples, this value being quite different from that corresponding to pure V 2 O 5 (VTO). Possible explanations for this observation are based on (i) the relative magnitudes of the V/Ti surface ratios and (ii) the presence of Ti 4+ in V 2 O 5 crystals.